Morbillivirus and coronavirus survey in stranded cetaceans, Brazil. - Samira Costa-Silva; Carlos Sacristán; Arícia Duarte-Benvenuto; Ana Carolina Ewbank; Rodrigo M Soares; Vitor L Carvalho; Pedro V Castilho; Marta J Cremer; Jenyffer V Vieira; Giulia G Lemos; Jéssica R Moreira; Gladys D Rogge Renner; et al. (PLoS ONE)
Since 2010, Guiana dolphin morbillivirus (GDMV; family Paramyxoviridae, genus Morbillivirus, species Morbillivirus ceti, syn. Cetacean morbillivirus) is recognized as the cause of death of multiple cetacean species along the Brazilian coast, including an unusual mortality event in Rio de Janeiro state. Coronaviruses of the genus Gammacoronavirus (family Coronaviridae) have been previously detected in cetaceans in the northern hemisphere. After the emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the COVID-19 pandemic and with the potential to affect several mammal species, there is an increased concern about the risk of infection in aquatic mammals. The goal of this study was to molecularly screen the presence of morbillivirus and coronavirus infections in cetaceans stranded in several regions of the Brazilian coast in order to determine their occurrence rates, pathogenicity, and range of potentially susceptible cetacean species. We molecularly tested tissue samples of 118 cetaceans, belonging to 20 species, found stranded in Brazil, between 2015 and 2022. Overall, 2.5% (3/118) of the analyzed cetaceans were positive for GDMV infection: a Guiana dolphin (Sotalia guianensis), an Atlantic spotted dolphin (Stenella frontalis), and a humpback whale (Megaptera novaeangliae). None of the animals were positive for coronavirus. Our findings indicate that the morbillivirus sequence type identified in Indo-Pacific bottlenose dolphins (Tursiops aduncus) of Australia and our GDMV sequences from Brazil belong to the same strain. The systematic monitoring of cetacean morbilliviruses is recommended to properly estimate the occurrence rate, pathogenicity and evolution of these viruses, which may help anticipate novel epizooties and reduce their impact on endangered cetacean populations.